Design a‏ ‏Rubber Seal used in Self-drill Bolt from an old Tire Tube by ‎using Finite Element Analysis Method ‎ (Journal of University of Babylon for Engineering Sciences, 2024)
This paper looks for the possibility of using a seal, formed from an old truck’s tube, in self-drill bolt to mount sheets on solid frame. A general study of a seal’s strength in self-drill bolt is performed with Ansys workbench 2022R1, which is a finite element model software to analysis the stresses and deformations.  Two types of rubber’s seal are used in the analysis, Neoprene and Elastomer, the elastomer is an equivalent rubber of tire’s tube. The metal washer, which is a part of self-drill bolt and located above the seal, is involved in all the simulations.   Also, the shape of metal washer is considered in analysis for both rubber’s types. The shape used in the simulation are a semi conic and conic. Because there are several rubber’s types and metal washer’s shapes, five different modeling analyses are made with Workbench 2022R1. All dimensions and sizes of the parts in all modeling are taken from dimensions of the real parts available in local markets.  The results show the tube’s rubber is a good replacement and has the best results with conic metal washer. In the case of not using tube’s rubber, a Neoprene seal bonded to conic metal washer is a second good choice.  To make sure of the success of tube’s rubber, a simple experiment is made and its results approve, without debt, the possibility of using tube’s rubber as a seal.